ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN - Anshar Daud (AkMen JURNAL ILMIAH, 2011)
The primary focus of this study is to analyze the influence of social and culture, reference group marketing communication, personal factor, motivation, perception and attitude formation to costomer decision making. This study shows that 1)sosial-cultural give influence on personal factor, motivation and decision making but insignificant to perception and attitude formation; 2)reference group influences personal factor, motivation, perception, attitude formation and decision making; 3)marketing communication effects attitude formation and decision making, but has no infact on perception; 4)personal factor effects motivation, perception, attitude formation but does not influence decision making; 5)attitude formation contributes positive and significant impact on decision making.